From the Contemporary Anthroponymy of Novi Sad 1 – Personal Names of Male Children Born in Novi Sad in 2021 - Marković, Brankica Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper presents and analyzes the personal names of male children born in Novi Sad in 2021. The aim of the paper is to show which male names are popular today and whether fashion takes precedence over tradition when choosing a child’s name, as well as to determine the frequency of recorded names. Names are classified according to their origins, structures, and meaning. As no similar scientific research has been conducted in recent times, this study can be considered scientifically current and relevant, and it will make a modest contribution to the contemporary anthroponymy of Novi Sad.